Perceived Barriers to Success for Minority Nursing Students: An Integrative Review. (30th May 2012) - Loftin, Collette; Newman, Susan D.; Dumas, Bonnie P.; Gilden, Gail; Bond, Mary Lou
Abstract : The objective of this paper was to identify barriers to successful program completion faced by underrepresented minority nursing students. This paper reveals that minority nursing student's face multiple barriers to success including lack of financial support, inadequate emotional and moral support, as well as insufficient academic advising, program mentoring, technical support, and professional socialization. An additional theme—a resolve to succeed in spite of the identified barriers—was identified. This body of literature focuses solely on successful minority students' experiences, revealing a significant gap in the research. The findings of this paper highlight the need to create and maintain nursing programs capable of aggressively supporting minority student needs. Recommendations for future research are included.